Source process of the 2002 Denali fault earthquake compared to other large strike slip events - Fromm, Robert; Özacar, Atilla Arda; Beck, Susan L.; Christensen, Douglas (2003)
The November 3, 2002 Denali Fault earthquake which is the largest inland event ever recorded in central Alaska, occurred along an arcuate segment of the right-lateral strike-slip Denali Fault. We use fi rst motion P-wave polarities and the inversion of teleseismic P-waveforms to constrain the focal mechanism and rupture history. We fi nd clear evidence for a substantial reverse component at the beginning of the rupture, which can not be explained with a pure strike-slip mechanism. This initial subevent occurred along an asperity 20 km west of the hypocenter and can be attributed to thrusting along the Susitna Glacier Fault. Approximately, 10 sec after the fi rst asperity failed, the rupture propagated unilaterally to the east on a strike-slip fault and released most of the seismic moment along an asperity located 170 km east of the hypocenter, adjacent to the rupture transfer from the Denali Fault to the Toschunda Fault which bifurcates toward the southeast. This earthquake had a duration of ~120 sec and a total rupture length of ~320 km with a maximum slip of 8 m. Correlation with gravity anomalies suggests a relation between moment distribution and physical properties of the subsurface rock units that may support a weaker middle segment marked by fewer aftershocks. Moreover, both asperities coincide with intense gravity gradients possibly refl ecting a crustal boundary. We analyzed the aftershock distribution by estimating the number of events, released moment, and b-values within regular spaced bins along the rupture plane. Strong correlation with the obtained asperities and weakness zones are observed, suggesting different aftershock nucleation mechanisms for different segments of the fault. Comparison of this event with similar magnitude November 14, 2001 Kunlun earthquake (Tibet) in terms of rupture length, aftershock distribution, radiated energy, static stress drop, and tectonic setting; implies a stronger seismic coupling along the Denali fault. For a broader approach, large (Mw > 7.2) strike-slip ...